Prediction of Heart Rate in Football Using Inertial Measurement Units - Schnack, T.; Baca, A. (15. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie": Zwischen Geistesakrobatik und praktischer Anwendung: Innovationen in der Sportinformatik und Sporttechnologie, 2024)
Heart rate (HR) is a crucial measure for exercise intensity, yet its measurement in official football matches is challenging due to equipment restrictions. This study aims to predict HR time series based on player kinematics. Data was collected from five professional football players during a friendly match. Six prediction models were com-pared to one another. The results demonstrate the potential of kinematic data to pre-dict HR in football, although further research with larger sample sizes and advanced models is needed to enhance prediction accuracy and practical applicability.